The impact of a State-sponsored irrigation project on Karrayu Pastoralists in Ethiopia - Tefera Goshu; Ayalew Gebre (Cogent Social Sciences, 2023)
This article examines how a project intended to help local pastoralists facilitates the accumulation of wealth among elites at the expense of the local people. The data was collected qualitatively from five villages classified spatially based on the variability of water availability and access along the catchment. It was gathered through in-depth interviews, focus group discussions, and observation, which were then analyzed using a thematic data analysis strategy. The findings indicate that the Project associated with privatising communal land has transformed land-related social and production relationships. It has been characterisedby the development ofexploitative sharecropping arrangements involving multiple actors and marketing relationships. Landowners pastoralists have marginally benefited while capitalists maximize wealth without dispossessing the locals from their land, i.e., accumulation without dispossession. The study concludes that the Project served as a tool to reinforce local exploitation by dispossessing profit gains from their land while allowing external investors to grow and prosper. Finally, the article suggests a policy implication aimed at strengthening households’ capacity so that local pastoralists can farm independently on their land and reap the full benefits.